2022
DOI: 10.3390/ma15227988
|View full text |Cite
|
Sign up to set email alerts
|

Strength Prediction of Ball-Milling-Modified Phosphorus Building Gypsum Based on NSGM (1,4) Model

Abstract: Phosphogypsum is an industrial byproduct from the wet preparation of phosphoric acid. Phosphorus building gypsum can be obtained from phosphogypsum after high-thermal dehydration. This study aimed to analyze the influence of ball milling with different parameters on the strength of phosphorus building gypsum. In this paper, the absolute dry flexural strength and the absolute dry compressive strength of phosphorus building gypsum were compared under different mass ratios of material to ball, ball-milling speed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Fernández-Álvarez et al [9] revealed that adding nanosilica to milling process makes the epoxy-matrix coatings degrade chemically less than the non-reinforced ones under irradiation and thus wear resistance. Zhang et al [10] predict the influence of ball milling with different parameters on the strength of phosphorus building gypsum by using NSGM (1,4) Model. Attyabi et al [11] studied the effect of time on microstructure and magnetic properties of Mn52Al45.7C2.3 flakes with different sizes fabricated using a ball-milling method.…”
Section: Introductionmentioning
confidence: 99%
“…Fernández-Álvarez et al [9] revealed that adding nanosilica to milling process makes the epoxy-matrix coatings degrade chemically less than the non-reinforced ones under irradiation and thus wear resistance. Zhang et al [10] predict the influence of ball milling with different parameters on the strength of phosphorus building gypsum by using NSGM (1,4) Model. Attyabi et al [11] studied the effect of time on microstructure and magnetic properties of Mn52Al45.7C2.3 flakes with different sizes fabricated using a ball-milling method.…”
Section: Introductionmentioning
confidence: 99%